Teaching content management in technical and professional communication - Bridgeford, Tracy 1960- (New York, NY Routledge, 2020)
Teaching content management in technical and professional communication offers a comprehensive overview of approaches to teaching the complex subject of content management. The book defines and explains content management and its accompanying competencies, providing teaching examples in areas including content strategy, topic-based writing, usability studies, and social media. It covers tasks associated with content management such as analyzing audiences and using information architecture languages including XML and DITA. The book also highlights the communal aspects of content management, focusing on the work of writing stewardship and project management, and the characteristics of content management in global contexts. It concludes with a look to the future and the forces that shape content management today. The editor situates the collection within a pedagogical exigency, providing sound instructional approaches to teaching content management from a rhetorical perspective. The book is an essential resource for both instructors new to teaching technical and professional communication, and for experienced instructors who are interested in upgrading their pedagogies to include content management"--
Reconceptualizing technical communication pedagogy in the context of content management / George Pullman, Georgia State University, Baotong Gu, Georgia State University -- Content Management : Where the ideal world of technical communication in academia meets the realities of the workplace / Saul Carliner, Concordia University -- Teaching content strategy in technical communication / Liza Potts, Michigan State University, Laura Gonzales, The University of Florida.
Includes bibliographical references and index (232-235)
Keywords: Communication of technical information -- Study and teaching